Comparative Analysis of Waterwheel Efficiency Using Nozzle and Open Canal on Waterway - Soleh Pohan, Abdul Rahman; Mugisidi, Dan; Nurfadillah, Zaka; Heriyani, Oktarina (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2023)
Water flow in irrigation is a means of obtaining electric power, which is commonly called microhydro. The waterwheel is the main component of the microhydro energy conversion process. The amount of energy converted by a waterwheel depends on the shape of its model, blade shape and the location of the installer. This study aimed to identify the characteristics of optimally efficient waterwheels. In addition to the energy of the place (i.e., the head), the influence of the weight of the water flowing into the blades of the waterwheel must be considered. This study also aimed to determine the effectiveness of mill performance by comparing waterways that use nozzles with those that use open canals. An experimental method was used to design a waterwheel system by testing the efficiency ratio between the nozzle line and the open canal. This test used the following variable water discharge rates: 12 m3/hr, 14 m3/hr, 16 m3/hr, 18 m3/hour and 20 m3/hr. Using the nozzle line with the largest discharge rate of 20 m3/hr, an rpm of 192.7 is produced with a torque of 0.7 Nm. The waterwheel produced 14.13 watts, with an efficiency of 64.75%. A line that used an open channel at the highest discharge rate of 20 m3/hr produced 61.7 rpm with 0.7 Nm of torque and 4.52 watts with an efficiency of 20.71%. The speed of water flow in the nozzle line was faster than in the open canal path, causing the tangential force on the waterwheel to be greater than on the open canal path. Based on these results, it was concluded that the path was the most efficient when using a nozzle.